SYAFIQ RIZA HASAN BASALAMAH'S DA'WAH STRATEGY IN FORTIFYING MUSLIM FAMILIES FROM LGBT DEVIATION IN THE ERA OF SOCIETY 5.0 - Rizky Fachri Zain, Bayu; Yassir, Muhammad (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
The Society 5.0 era brings new challenges to Muslim families, particularly in facing the widespread normalization of LGBT ideologies through digital media and educational systems. This study analyzes these challenges and the da'wah strategies employed by Ustaz Syafiq Riza Hasan Basalamah in protecting Muslim families from LGBT influence. Using a descriptive-qualitative approach through literature review and direct interviews, the findings show that his da'wah strategies encompass strengthening tauhid, continuous preaching, active family involvement, digital media engagement, and counter-narratives to LGBT ideology. His approach is flexible, educational, and solution-oriented, emphasizing the role of the state and educational institutions. The study concludes that the moral resilience of Muslim families depends on structured da'wah rooted in authentic Islamic values.